(3CMcGe NWhW Gdcas - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3ZPG hLOJ NWhW Gdca eSJhjI MSfg fGbV dUGMHgG HWhd GdYeQ s
(3BNQgG (B:s
(3hjSJYed cd KdGKI eQI aEf Ccdg dGjLhY hdG jYWT eOI KdGKI CjGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3GfXQ GdeNWhW Qbe (B170s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(4 / 3381) s
Keywords: (3GdaQGSIs